Boiling of the new low-GWP refrigerants R1234ze(Z) and R1233zd(E) inside a small commercial brazed plate heat exchanger. (August 2019) - Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio
Highlights: This paper investigates R1234ze(Z) and R1233zd(E) vaporisation inside a BPHE. R1234ze(Z) exhibits boiling heat transfer coefficients 17–22% higher than R1233zd(E). R1234ze(Z) exhibits frictional pressure drops 7–32% lower than R1233zd(E). R1234ze(Z) and R1233zd(E) are very promising as low GWP fluids for HTHP and ORC. Abstract: This paper presents the heat transfer coefficients and the frictional pressure drops of R1234ze(Z) and R1233zd(E) boiling inside a commercial Brazed Plate Heat Exchanger (BPHE): the effects of heat flux / mass flux, saturation temperature / pressure, outlet conditions and fluid properties are investigated. The boiling heat transfer coefficients are controlled mainly by heat flux / mass flux and evaporator outlet conditions. The degrees of superheating at the outlet of the evaporator produces a degradation of the average boiling heat transfer coefficient in the whole evaporator, particularly for R1234ze(Z). The frictional pressure drops exhibit a quadratic dependence on refrigerant mass flux. Saturation temperature / pressure has a remarkable influence only on the frictional pressure drops. R1234ze(Z) exhibits boiling heat transfer coefficients higher and frictional pressure drops lower than those of R1233zd(E). There is a reasonable agreement between the saturated boiling heat transfer coefficients and the calculated values by two recent models for boiling inside BPHE.